PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKABERBASIS MASALAH (PROBLEM BASED LEARNING) UNTUK SISWA SMP KELAS VIII PADA POKOK BAHASAN SISTEM PERSAMAAN LINEAR DUA VARIABEL (SPLDV) - Insani, Karuniaji Fitra; Suharto, S; Kristiana, Arika Indah (KadikmA, 2014)
Abstract.The research aims to know the process and result of development of mathematics problem based learning materials foreighth grade of junior high schoolforSystem of linear equations of two variablestopic. The products refer to the component of problem based learning. Learning instrumentsdevelopment model refers to Plomp models which has 5 steps namely (1) preliminary investigation, (2) design, (3) realization/construction, (4) test, evaluation, and revision and(5) implementation.This research has three products namely lesson plan, worksheet,and evaluation test. The data collection methods used in this research is, test interview, documentation, observation,and questionnaire.Based on the validation process and try out of validated materials, the score of each product are 0.93 for lesson plan, 0.94 for worksheet, and 0.95 for instrument. It can be concluded that the validated materials have satisfied of the validity, practice, and effective criteria. Key Words:Plomp models, problem based learning, System of linear equations of two variables